Recycling for a purpose in the late Lower Paleolithic Levant: Use-wear and residue analyses of small sharp flint items indicate a planned and integrated subsistence behavior at Qesem Cave (Israel). Issue 131 (June 2019) - Venditti, Flavia; Nunziante-Cesaro, Stella; Parush, Yoni; Gopher, Avi; Barkai, Ran
Abstract: The purposeful production of small flakes is integral to the lithic variability of many Middle Pleistocene sites. Inhabitants of the Acheulo-Yabrudian site of Qesem Cave, Israel, systematically recycled 'old' discarded blanks and tools, using them as cores for the production of small sharp tools with distinct technological features. These recycling end-products were produced in significant quantities throughout the human occupation of Qesem Cave, and their outstanding state of preservation made possible a functional analysis with residue detection using Fourier transform infrared spectroscopy (FTIR) and energy-dispersive X-ray spectroscopy (SEM-EDX). An experimental program accompanying the study tested the efficiency of each tool category, and a reference collection of the organic remains was assembled. Our integrated results show that small flakes were used mainly to process soft to medium animal material through precise cutting activities that required accurate longitudinal motions. Several items show clear and exclusive contact with bone while others were used for designated steps in hide treatment processes. Plant and tuber processing are also evidenced although to a lesser extent. We show that the end products of recycling 'old' flakes reflect preconceived technological and functional characteristics produced in a targeted manner to obtain specific tools designated for anticipated practical tasks. We demonstrate the complementary role of the products of recycling within the Qesem Cave tool-kits alongside larger tools in assisting early humans in the different stages of processing animal materials. Moreover, use-wear and residue evidence indicates that Qesem hominins differentiated their activities across space in the cave. We argue that the meticulous realization of specific tasks and the deliberate, repetitive, and skilled production of tools of different sizes and shapes is one characteristic of the new mode of adaptation practiced by Acheulo-Yabrudian hominins in the Levant in order to better manipulate the available resources following the disappearance of mega-herbivores.